2022
DOI: 10.3390/antibiotics11101385
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Small Molecule That Inhibits the Interaction of LPS Transporters LptA and LptC

Abstract: The need for novel antibiotics has become imperative with the increasing prevalence of antibiotic resistance in Gram-negative bacteria in clinics. Acting as a permeability barrier, lipopolysaccharide (LPS) protects Gram-negative bacteria against drugs. LPS is synthesized in cells and transported to the outer membrane (OM) via seven lipopolysaccharide transport (Lpt) proteins (LptA–LptG). Of these seven Lpt proteins, LptC interacts with LptA to transfer LPS from the inner membrane (IM) to the OM, and assembly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Thereafter, 2000 ns MD simulations were conducted on IMB-881 and IMB-0042 with LptA or LptC complex. It can be observed that the two molecules underwent multiple cycles of dissociation and reassociation throughout the entire 2000 ns simulation (Figure 9) as well, which is consistent with their slow-binding-slow-dissociation kinetic characteristics obtained by surface plasmon resonance (SPR) [11,12,21].…”
Section: Molecular Dynamics Simulationsupporting
confidence: 80%
See 1 more Smart Citation
“…Thereafter, 2000 ns MD simulations were conducted on IMB-881 and IMB-0042 with LptA or LptC complex. It can be observed that the two molecules underwent multiple cycles of dissociation and reassociation throughout the entire 2000 ns simulation (Figure 9) as well, which is consistent with their slow-binding-slow-dissociation kinetic characteristics obtained by surface plasmon resonance (SPR) [11,12,21].…”
Section: Molecular Dynamics Simulationsupporting
confidence: 80%
“…Currently, two molecular inhibitors (IMB-881 and IMB-0042) (Figure 2) that target the LptA and LptC interaction have been reported, but the precise molecular mechanisms are currently unclear [12,13]. Another peptide inhibitor, Thanatin, targeting the interaction between LptA and LptC, was also reported [14,15], and the co-crystal structure of Thanatin and LptA was solved to indicate the binding pose (PDB ID: 6GD5) [16].…”
Section: Introductionmentioning
confidence: 99%
“…The Y3H is an extension of the Y2H but introducing a third hybrid component, usually a small molecule that can make possible or interfere with the protein-protein interaction, or a RNA molecule allowing the detection of protein-RNA interactions. All these methods allow the study of interactions between proteins of any other biological origin in the yeast model; for this reason, the Y2H has been extensively used in pharmacological screenings for novel drugs [23,24].…”
Section: Yeasts As Biological Toolsmentioning
confidence: 99%